2021
DOI: 10.1002/art.41634
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Autoantibodies and Thrombosis in Patients With COVID‐19: Comment on the Article by Bertin et al

Abstract: | 897 situations (6), these data suggest that regulatory policy in each country influenced the use of HCQ/CQ for COVID-19.What can we learn from the differing experiences in New Zealand and the US? When potential medications for COVID-19 are proposed for clinical use without RCT evidence of efficacy and safety, strong regulatory action to restrict access circumvents excessive medication dispensing that may cause shortages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Irrespective, as for the case with LA, 11 there was also a large body of publications related to solid-phase aPL. 31 32 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Although additional relevant papers are likely available in the literature, the captured articles are sufficient for us to critically review the main literature to date. As for LA, 11 there was a wide variety of methods employed to identify solid-phase aPL ( Table 1 ), but sometimes the methodology was not reported.…”
Section: Results Of the Literature Review: Is Apl Present In Covid-19?mentioning
confidence: 99%
“…Irrespective, as for the case with LA, 11 there was also a large body of publications related to solid-phase aPL. 31 32 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Although additional relevant papers are likely available in the literature, the captured articles are sufficient for us to critically review the main literature to date. As for LA, 11 there was a wide variety of methods employed to identify solid-phase aPL ( Table 1 ), but sometimes the methodology was not reported.…”
Section: Results Of the Literature Review: Is Apl Present In Covid-19?mentioning
confidence: 99%
“…Some studies have found a high prevalence of aPL [ 6 •, 18 , 23 , 37 , 43 , 57 ] while others found a low prevalence and this could be linked to disease severity [ 19 , 24 , 26 , 35 •, 42 , 45 , 55 ]. Xiao et al found aPL in 31 out of 66 patients requiring ICU admission but not in patients with noncritical conditions [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, others studies did not confirm these results. Ferrari et al found a similar prevalence for LA, aβ 2 -GPI and aCL in severe and non-severe COVID-19 patients [ 43 ], and other authors did not find more aPL (aCL or aβ 2 -GPI) between patients with COVID-19 related acute respiratory disease syndrome and patients with pneumonia-associated acute respiratory disease syndrome in ICU [ 19 , 53 ]. One study did not find more LA in COVID-19 non-survivors than in survivors [ 32 ], likewise other studies did not find any association between overall aPL positivity and in-hospital mortality [ 50 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, our observation that no patient had antibodies to β2-GP1 (an APS criteria antibody) or to domain 1 β2-GPI (reportedly higher specificity for APS) argues against the presence of APS in our cohort. In a study of 37 COVID+ acute respiratory disease versus 31 pre-pandemic (not contemporaneous) acute respiratory disease controls using a sample collected within 48 hours of admission, Frapard, et al reported that 37 COVID patients exhibited more thrombotic events as compared to 31 pre-pandemic controls but the occurrence of APLA in the two groups was similar 20 . Using APLA assays similar to ours, Borghi, et al .…”
Section: Discussionmentioning
confidence: 99%